Remote and rural dementia care policy, research and practice - Innes, Anthea 1973-; Morgan, Debra ca. 20./21. Jh; Farmer, Jane 1964- (Policy Press, 2020)
As the number of people affected by dementia continues to rise, this is the first in-depth examination of related services dedicated to the unique demands of remote and rural settings. Contributors from the UK, Australia, North America and Europe explore the experiences and requirements of those living with dementia and those caring for them in personal and professional capacities in challenging geographical locations. For practitioners, researchers, academics and policy makers, this book is an essential review of evidence and strategies to date, and a guide to future research needs and opportunities for improvements in rural dementia practice